2006
DOI: 10.1111/j.1365-2362.2006.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein apolipoprotein A‐I kinetics: comparison of radioactive and stable isotope studies

Abstract: To compare the kinetic determinants of high-density lipoprotein (HDL) apolipoprotein A-I (apoA-I) concentration in lean normolipidaemic subjects using radioisotope and stable isotope studies. We pooled data from 16 radioisotope and 13 stable isotope studies to investigate the kinetics of apoA-I in lean normolipidemic individuals. We also examined the associations of HDL kinetic parameters with age, sex, body mass index (BMI) and concentrations of apoA-I, triglycerides, HDL cholesterol and low-density lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Similarly, there is no difference between normotriglyceridemic (plasma TG concentration < 185 mg/dl) men and women in IDL-apoB-100 and LDL-apoB-100 kinetics,62,63 consistent with the absence of sex differences in IDL and LDL subfraction concentrations and LDL subclass distribution and particle size. Studies evaluating HDL-apoA-I and apoA-II kinetics generally report some6466 or no62,67,68 differences between men and women, indicating relatively small effects on HDL metabolism. Clearly, more kinetic studies are needed to better understand the mechanisms responsible for the observed effects of obesity and sex on plasma lipoprotein profile.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is no difference between normotriglyceridemic (plasma TG concentration < 185 mg/dl) men and women in IDL-apoB-100 and LDL-apoB-100 kinetics,62,63 consistent with the absence of sex differences in IDL and LDL subfraction concentrations and LDL subclass distribution and particle size. Studies evaluating HDL-apoA-I and apoA-II kinetics generally report some6466 or no62,67,68 differences between men and women, indicating relatively small effects on HDL metabolism. Clearly, more kinetic studies are needed to better understand the mechanisms responsible for the observed effects of obesity and sex on plasma lipoprotein profile.…”
Section: Discussionmentioning
confidence: 99%
“…Additional insights into these labeling techniques have been detailed previously. 50,51 Gas Chromatography Versus Liquid Chromatography-Mass Spectrometry Applied to Endogenous Labeling Mass spectrometry is required to detect stable isotope tracer in proteins. Subjects are usually administered a stable isotope-labeled amino acid (eg, trideuterated leucine [D3-Leu]) by constant infusion or by bolus, which is in turn taken up by tissues and then incorporated into nascent proteins, some of which are secreted into circulation.…”
Section: Exogenous Versus Endogenous Labeling Of Hdl Proteinsmentioning
confidence: 99%